An exploratory study of the occupational mobility patterns of African American women working in public sector parks and recreation organizations in the United States. Issue 6 (1st November 2020) - Waller, Steven N.; Wozencroft, Angela J.; Scott, Jason L.; Shaw, Sonya; Picariello, Manuela
ABSTRACT: Research Question: The purpose of this study was to provide an update on the status of African American working women in public parks and recreation (city and county) in the United States. Three research questions guided this study: (1) What is the occupational mobility pattern for the sample of African American female public parks and recreation employees from 2010–2015?; (2) Is there a relationship between select demographic variables and occupational mobility within the sample population?; and (3) What are the sample population's perceptions about race and gender as potential barriers to occupational mobility? Research Methods: A 50-item e-survey was developed utilizing Qualtrics and was sent to study participants via e-mail. The survey contained three sections: (1) perceived status (importance of the position in the organization) of 17 common occupational titles; (2) information about occupational mobility; and (3) demographic information. The occupational titles used in the present study were consistent with the titles used in previous occupational mobility studies in public parks and recreation and in previous National Recreation and Park Association salary surveys. Results and Findings: Overall, the majority of the sample (79.6%, n = 90) did not experience any mobility between 2010–2015; 16% (15.9%, n = 18) were upwardly mobile, and the remaining 4.4% ( n = 4) experienced downward mobility. A weak but significant association was found between the variables mobility pattern and position type [ X 2 (6, N  = 113) = 13.20, p  = .04; V  = .24]. However, no significant associations were found between mobility pattern, age, number of years of experience in public parks and recreation, marital status, minor children at home, educational level and income, respectively. When the respondents were asked whether they were presently seeking a position that they felt would be a career advancement, 53.1% ( n = 60) indicated "yes" while the remaining 46.9% ( n = 53) responded "no". Implications: The respondents in the study indicated that their race or gender served as a facilitator or deterrent to occupational mobility. The women in this study were interested in advancing their careers, but considered multiple factors before pursuing opportunities. In order to more accurately examine career mobility "exit" data should be examined.